The Role of Stakeholder in Fostering Traditional Art Awareness (A Case Study of Sundanese Local Song âCianjuranâ Artist Training in Sumedang Regency West Java, Indonesia) - Julia, Julia (Harmonia: Journal of Arts Research and Education, 2016)
This paper examines the process of seeding or training of Sundanese Song Cianjuran by artists in Sumedang regency that is conducted by a stakeholder of Sundanese traditional arts. The study was conducted using descriptive analytic methods, and data collection was done through observation and interviews. Results from the study explained that stakeholder participation was vital and influential towards the existence of Sundanese Song Cianjuran, especially in growing cultural awareness and in generating candidates for local traditional artists.How to Cite: Julia. (2016). The Role of Stakeholder in Fostering Traditional Art Awareness (A Case Study of Sundanese Local Song âCianjuranâ Artist Training in Sumedang Regency West Java, Indonesia). Harmonia: Journal of Arts Research And Education, 16(1), 87-94. doi:http://dx.doi.org/10.15294/harmonia.v16i1.6005Â